Long-term safety and efficacy of subcutaneous immunoglobulin IgPro20 in CIDP: PATH extension study. Issue 5 (September 2019) - van Schaik, Ivo N.; Mielke, Orell; Bril, Vera; van Geloven, Nan; Hartung, Hans-Peter; Lewis, Richard A.; Sobue, Gen; Lawo, John-Philip; Praus, Michaela; Durn, Billie L.; Cornblath, David R.; Merkies, Ingemar S. J.
Abstract : Objective: To investigate the long-term safety and efficacy of weekly subcutaneous IgPro20 (Hizentra, CSL Behring) in chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: In a 48-week open-label prospective extension study to the PATH study, patients were initially started on 0.2 g/kg or on 0.4 g/kg weekly and—if clinically stable—switched to 0.2 g/kg weekly after 24 weeks. Upon CIDP relapse on the 0.2 g/kg dose, 0.4 g/kg was (re)initiated. CIDP relapse was defined as a deterioration by at least 1 point in the total adjusted Inflammatory Neuropathy Cause and Treatment score. Results: Eighty-two patients were enrolled. Sixty-two patients initially received 0.4 g/kg, 20 patients 0.2 g/kg weekly. Seventy-two received both doses during the study. Sixty-six patients (81%) completed the 48-week study duration. Overall relapse rates were 10% in 0.4 g/kg–treated patients and 48% in 0.2 g/kg–treated patients. After dose reduction from 0.4 to 0.2 g/kg, 51% (27/53) of patients relapsed, of whom 92% (24 of 26) improved after reinitiation of the 0.4 g/kg dose. Two-thirds of patients (19/28) who completed the PATH study without relapse remained relapse-free on the 0.2 g/kg dose after dose reduction in the extension study. Sixty-two patients had adverse events (AEs) (76%), of which most were mild or moderate with no related serious AEs. Conclusions: Subcutaneous treatment with IgPro20 provided long-term benefit at both 0.4 and 0.2 g/kg weekly doses with lower relapse rates on the higher dose. Long-term dosing should be individualized to find the most appropriate dose in a given patient. Classification of evidence: This study provides Class IV evidence that for patients with CIDP, long-term treatment with SCIG beyond 24 weeks is safe and efficacious.